2017
DOI: 10.18632/oncotarget.19576
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic modeling of oral cancer by gene profiles and clinicopathological co-variables

Abstract: Accurate staging and outcome prediction is a major problem in clinical management of oral cancer patients, hampering high precision treatment and adjuvant therapy planning. Here, we have built and validated multivariable models that integrate gene signatures with clinical and pathological variables to improve staging and survival prediction of patients with oral squamous cell carcinoma (OSCC). Gene expression profiles from 249 human papillomavirus (HPV)-negative OSCCs were explored to identify a 22-gene lymph … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 33 publications
0
27
0
1
Order By: Relevance
“…Previous attempts to biologically classify HNSCCs have mostly relied upon analyses incorporating known patient outcomes to identify mutations and/or differentially expressed genes that correlated with worse survival (25,28,(31)(32)(33). In contrast, fewer studies have used unbiased strategies to classify HNSCCs into distinct biological subtypes that would predict different biological outcomes (26,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Previous attempts to biologically classify HNSCCs have mostly relied upon analyses incorporating known patient outcomes to identify mutations and/or differentially expressed genes that correlated with worse survival (25,28,(31)(32)(33). In contrast, fewer studies have used unbiased strategies to classify HNSCCs into distinct biological subtypes that would predict different biological outcomes (26,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…The validity of this diagnostic microarray was verified by a study on a large number of samples of cN0 OSCC patients, achieving high performance with 86% sensitivity and 89% negative predictive value (NPV) for assessing LNM; this is almost on par with the performance of SLNB [ 109 ]. Recently, the 22-gene LNM signature identified by another study with a large number of samples was applied to pretreatment evaluation of early-stage OSCC patients and effectively reduced the rate of overtreatment by two-thirds [ 110 ].…”
Section: New Yardstick For Diagnosis and Treatment Assessmentmentioning
confidence: 99%
“…Data set GSE30788/GSE85446 consists of 150 Dutch patients (of which 60 presented a LNM and 90 did not) with a HPV-negative oral cancer tumor who are in that respect similar to the TCGA patients. Gene expression was measured by microarray, the p -values on GSE30788/ GSE85446 were calculated using a Welch two-sample t-test; further details on the study can be found in [ 29 ]. The differences between the TCGA and the Dutch data (notably the platform and the geographical location of the patients) preclude a straightforward meta-analytic data integration.…”
Section: Applicationsmentioning
confidence: 99%
“…After training the base RF and the CoRF, we validate these classifiers on an independent data set (GSE84846). GSE84846 contains microarray expression data of 97 HPV-negative oral cancer patients from Italy, of whom 49 had a LNM [ 29 ]. To directly apply the classifiers to the validation data, we need to account for the differences in scale between RNASeqv2 and microarray data.…”
Section: Applicationsmentioning
confidence: 99%